KONTEKSTUALISASI HADIS PEMINANGAN PEREMPUAN TERHADAP LAKI-LAKI - Masduki, Masduki (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
This article is talking about the contextual understanding of Hadith about women proposing toward men and how this phenomenon develops in the contemporary era. Islam requires that a proposing is done before marriage. The practice of proposing generally is held by men. However, in several locations, it is found that a proposing is committed by women. They are doing it because of their understanding of a hadith which explains that in Islam, a woman has the right to propose a man. On the other side, Islam does not regulate who must propose whether men or women. Even though, there is a hadith which tells that a woman offered her self to be married by a pious man. As an open and changed text, a hadith can be explained by many ways of interpretation. One of them is contextual understanding. Therefore, contextual understanding of woman proposing toward a man which is based on the hadith is allowed because the prophet did not give a legal decision and forbid it.Â Keywords: Hadith, Women Proposing, Contextual Understanding